Graphene-bacteria composite for oxygen reduction reaction - Kang, Horng Uei (2015)
Due to the unique array of properties displayed by graphene such as high specific surface area and good electrical conductivity, it is extensively researched and is a promising material for the practical applications such as fuel cells. However, there are some drawbacks limiting its application, for instance lacking of intrinsic catalytic ability and the usage of hazardous chemicals to reduce graphene oxide (GO). Hence, in this study, an eco-friendly and feasible method is developed to synthesize carbonaceous graphene by using E. coli as reducing agent, spacers and doping precursors then the electrocatalytic ability of product is investigated. The formation of reduced graphene oxide (rGO) is confirmed by Raman and Fourier transform infrared spectroscopy (FTIR) due to the restoration of C=C and decline of C=O. Through scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET) model, bacteria acting as spacers is showed. The pyrolysis of bacteria leads to heteroatom doping and is proved by X-ray photoelectron spectroscopy (XPS). Cyclic voltammetry (CV) and linear sweep voltammetry (LSV) also shown that the electrocatalytic ability of rGO – E. coli composite also improved by having lower onset potential and higher current density. By plotting Koutecky-Levich plot, a nearly ideal four-electron pathway is obtained. The composite also showed its durability after continuous operation and tolerance to methanol. In conclusion, the doped graphene produced from green method showed its enhanced electrocatalytic ability for ORR. This opens up more possibilities for other energy-related applications.